2015
DOI: 10.1136/ebmed-2015-110250
|View full text |Cite
|
Sign up to set email alerts
|

How does evidence affect clinical decision-making?

Abstract: In 1998, the "Evidence Cart" was introduced to provide decision-support tools at the point of care. A recent study showed that a majority of doctors who previously stated that evidence was not needed sought it nevertheless when it was easily available. In this study, invited clinicians were asked to rate the usefulness of evidence provided as abstracts and "the bottom-line summaries" (TBL) using a modified version of a Web app for searching PubMed and then specify reasons how it might affect their clinical dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 16 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…The ability to use information-seeking behavior with specific clinical questions, methods, and reliable websites are important to clinicians [ 1 , 2 ]. A survey of clinicians by White et al [ 3 ] found that only 65% used PubMed often.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ability to use information-seeking behavior with specific clinical questions, methods, and reliable websites are important to clinicians [ 1 , 2 ]. A survey of clinicians by White et al [ 3 ] found that only 65% used PubMed often.…”
Section: Introductionmentioning
confidence: 99%
“…Wireless mobile devices can alleviate barriers to access and improve delivery of reliable clinical information to support clinical decision making at the point of care. Fontelo and colleagues [ 1 ] noted that clinicians using a Web version of PubMed4Hh [PubMed for Handhelds] preferred “bottom-line summaries” more than abstracts. The PubMed4Hh mobile application can be useful for providing clinicians with a quick way to access online biomedical literature in support of evidence-based medicine at the point of care if it is integrated into clinical workflow.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations